CNC software by using Visual Basic / Eka Syabireen Hassan - Hassan, Eka Syabireen (1999)
As time passes, the connection between Mechanical and Information Technology is increasing bonding. Many of Mechanical applications such as Heat Transfer, Fluid Mechanics, Mechanical Design, etc. has been combined with Information Technology to decrease time solving problems. This all can be done by using Computer to solve long equation in the matter of seconds. In Malaysia, the Technology of Computer is increasing start from 1993. Since then the information from the whole world gets in Malaysia just in a second. As the fast changes of Information Technology, Mechanical Technology also would follow up. As example, manual technical drawing now can be drawn by using computer like AutoCAD, UniGraphics, Microstation and many others more application. This will decrease of drawing time as if there is a mistake in drawing, it can be altered easily. Other's application like element analysis, heat distribution, air flow (fluid analysis) and all in the Mechanical application is converted into Information Technology to make the work easier for modern engineer. Industrial developments also follow UD the technology as manufacturing is getting easier by the help of computers. More precision product can be produce as the machine is controlled by computers that can control more than 3 movement simultaneously. Knowledge of programming in computer is needed to established one mechanical application into Information Technology. This Final Project is a study of how to programming a CNC Software by using Visual Basic. Student in Bachelor Engineering (Hon's) in Mechanical at UiTM has learn to programming in FORTRAN in Semester 1 and Semester 2. Where we try to take some application and convert it into a programming that makes a task easier and takes a shorter time to solved. But as Microsoft introduce its product "Microsoft Visual Basic" which this language is made for 32 bit application and the important is the language is easier to learn than others. Beside its easy programming language, it's also can manipulate Windows Platform which makes it one of the powerful language programming.